Adaptive Human Resource Management Strategies during Global Crises in the Tourism Industry - Mari Maryati; Rita Sari Puspita; Umi Narimawati; Bobi Kurniawan (Economics and Business Journal (ECBIS), 2026)
The uncertainty surrounding the global economy has created existential challenges for the tourism industry, necessitating a Human Resource Management (HRM) paradigm that goes beyond traditional administrative approaches. This study aims to explore adaptive HRM strategies in the face of the global crisis, with a particular focus on the highly vulnerable tourism and hospitality industries.This study uses the PRISMA framework to conduct a systematic literature review of 26 peer-reviewed articles published between 2023 and 2025, sourced from Google Scholar. The findings indicate that effective adaptive strategies require the holistic integration of e-HRM and Artificial Intelligence (AI) to enhance operational agility, the implementation of GHRM to drive efficiency and employee retention, and the development of Agile Leadership to navigate uncertainty. Furthermore, this study highlights the crucial role of prioritizing employee well-being and Psychological Capital (PsyCap), particularly in emerging economies where social safety nets may be limited. This research provides a comprehensive framework for HR practitioners in the tourism sector to formulate policies that balance business continuity with human-centric support in challenging times.